2015
DOI: 10.11607/prd.2571
|View full text |Cite
|
Sign up to set email alerts
|

A Regenerative Approach to the Successful Treatment of Peri-implantitis: A Consecutive Series of 170 Implants in 100 Patients with 2- to 10-Year Follow-up

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
94
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(95 citation statements)
references
References 0 publications
1
94
0
Order By: Relevance
“…Eight prospective clinical studies [22,23,28,29,34,36,38,39], seven case series [24-27,30,33,35], and three randomized clinical trials (RCTs) [31,32,37] were included for the final review. A total of 528 patients (713 implants) were treated.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eight prospective clinical studies [22,23,28,29,34,36,38,39], seven case series [24-27,30,33,35], and three randomized clinical trials (RCTs) [31,32,37] were included for the final review. A total of 528 patients (713 implants) were treated.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies included rough surface dental implants [26,29,30,31,32,35,37,39], three studies investigated machined surface implants [23,24,36] and five studies - both rough and machined surface dental implants [22,25,27,28]. The remaining two studies did not reveal implant surface specifications [33,38].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…26,27,30,[34][35][36]38,39,42,49,50 The authors of the current review have noted that surface access may be a critical factor in accomplishing complete SDC. 64 Moreover, the studies showing the best outcomes for PD reduction (Roos-Jansaker, 30 Deppe et al 43 and Froum et al 27 ) with at least 3 years of follow-up and an initial osseous defect of .4 mm, used bone grafts and/or bone replacement graft layered by a barrier membrane. One study showed similar RBF (1.5 mm and 1.1 mm) using xenograft with and without coverage with a resorbable membrane, respectively.…”
Section: Discussionmentioning
confidence: 99%